Menemukan Akar Masalah dalam Penelitian Pendidikan: Antara Teori dan Realitas Lapangan - Nurhidayat Nurhidayat; Hamsa Hamsa; Rasti Pebry Pebry; Wan Ajijah; Saprin Saprin; Jamaluddin Majid (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
A research problem is the starting point and foundational core of any scientific inquiry, defined as the gap between ideal conditions and actual realities that demands resolution through research. This article critically examines how to identify the root of research problems in educational studies, especially in bridging the gap between theoretical frameworks and empirical realities in the field. Using a qualitative descriptive approach and library research methods, the study analyzes how valid and contextual research problems can be formulated through direct observation, critical reflection, and analytical tools such as the Five Why Technique and Fishbone Diagram. The findings reveal that many novice researchers in education still develop research problems using a top-down, theory-driven model without prior investigation of real issues in the educational context. The novelty of this article lies in its integrative approach, combining theoretical insights with field-based exploration, and emphasizing the need for flexibility in formulating research problems in qualitative studies. This article also offers systematic strategies for constructing specific, applicable, and socially relevant research problems. It is expected to serve as a methodological reference for researchers aiming to produce work that is both academically valid and practically impactful.